Unification of Marriage Law and Its Problems - Syahrul Syahrul; Evie Syalviana (LPPM IAIN Sorong, 2020)
Abstrak Law is a normative rule that govern human behaviors. The development of law as rule is not stagnant in one situation. But, its grew out from the awareness of society that requires the existence of law. Therefore, law always adopts the values that grow in society like; customary law, traditions and religions law. The consequences of laws as social and cultural products, even products of political ideology, making law is always contextual with the reality of society. This article try to understand the unification of marriage law in Indonesia and the problems that arise in the unification process. Unification is process of unify the laws in sociey or unify the national law in society. The article finds that there are many problems arising from the unification of marriage law in Indonesia, especially those related to interfaith marriages. So, it is not surprising that there are so many products of the marriage law probide the interfaith marriage in Indonesia, especially if interfaith marriage involves woman and man Muslims. Keyword: Interfaith Marriage, National Law, Islamic Law Abstrak Hukum adalah aturan-aturan normatif yang mengatur pola perilaku manusia. Hukum tidak tumbuh di ruang yang vakum, melainkan tumbuh dari kesadaran masyarakat yang membutuhkan adanya suatu aturan bersama. Karena itu, hukum selalu mengadopsi nilai-nilai yang tumbuh dan berkembang dimasyarakat; nilai-nilai adat, tradisi dan agama. Konsekuensi hukum sebagai produk sosial dan kultural, bahkan juga produk politik yang bernuansa ideologi, menjadikan hukum selalu bersifat kontekstual. Tulisan ini berusaha untuk mengungkap tentang unifikasi hukum perkawinan di Indonesia dan problematika yang muncul pada proses unifikasi tersebut. Unifikasi merupakan penyatuan hukum yang berlaku secara nasional atau penyatuan pemberlakuan hukum secara nasional. Penulis menemukan adanya banyak persoalan yang muncul dari unifikasi hukum perkawinan di Indonesia, khususnya yang terkait dengan perkawinan beda agama. Maka, tidak heran jika begitu banyak produk undang-undang perkawinan yang menjadi penghalang terjadinya nikah beda agama di Indonesia, khususnya jika melibatkan orang Islam. Kata Kunci: Pernikahan Beda Agama, Hukum Nasional, Hukum Islam